2010
DOI: 10.1074/jbc.m109.079921
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Complex of Transforming Growth Factor-β1 Reveals Isoform-specific Ligand Recognition and Receptor Recruitment in the Superfamily

Abstract: Transforming growth factor (TGF)-␤1, -␤2, and -␤3 are 25-kDa homodimeric polypeptides that play crucial nonoverlapping roles in embryogenesis, tissue development, carcinogenesis, and immune regulation. Here we report the 3.0-Å resolution crystal structure of the ternary complex between human TGF-␤1 and the extracellular domains of its type I and type II receptors, T␤RI and T␤RII. The TGF-␤1 ternary complex structure is similar to previously reported TGF-␤3 complex except with a 10°rotation in T␤RI docking orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
199
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(214 citation statements)
references
References 50 publications
10
199
1
4
Order By: Relevance
“…This suggests that mmTGF-␤2-7M functions to inhibit TGF-␤ signaling in the manner anticipated, which is by binding to and blocking endogenous T␤RII. The fact that the measured potency is greater than the greatest affinity previously reported for TGF-␤1 and TGF-␤3 binding to T␤RII (140 nM) (9), suggests that other factors, such as nonspecific association of mmTGF-␤2-7M with the plasma membrane, may serve to potentiate its inhibitory activity.…”
Section: Engineered Tgf-␤ Monomer That Blocks Tgf-␤ Signalingmentioning
confidence: 53%
See 3 more Smart Citations
“…This suggests that mmTGF-␤2-7M functions to inhibit TGF-␤ signaling in the manner anticipated, which is by binding to and blocking endogenous T␤RII. The fact that the measured potency is greater than the greatest affinity previously reported for TGF-␤1 and TGF-␤3 binding to T␤RII (140 nM) (9), suggests that other factors, such as nonspecific association of mmTGF-␤2-7M with the plasma membrane, may serve to potentiate its inhibitory activity.…”
Section: Engineered Tgf-␤ Monomer That Blocks Tgf-␤ Signalingmentioning
confidence: 53%
“…The structures of the TGF-␤ receptor complexes (8,9), as well as accompanying binding and cross-linking studies with TGF-␤3 C77S (7,8,37), suggested that the signaling capacity of monomeric TGF-␤s (TGF-␤1 C77S or mTGF-␤1 and TGF-␤3 C77S or mTGF-␤3) arise from their ability to non-covalently dimerize and in turn bind their receptors (Fig. 1, A and C).…”
Section: Design Of Engineered Mini-monomeric Tgf-␤ (Mmtgf-␤)mentioning
confidence: 99%
See 2 more Smart Citations
“…The TGF-b molecule resembles two hand-like structures that are assembled in an antiparallel manner and are held together by a disulfide bond in the "wrist" region. TGF-b contacts TbRI with the "fingertips" and TbRII with the underside of the fingers (Hart et al 2002;Groppe et al 2008;Radaev et al 2010). In addition, direct receptor-receptor interactions contribute to enhanced stability of the receptor-ligand complex (Radaev et al 2010).…”
Section: Tgf-b Signals Via a Heterotetrameric Tbri † Tbrii Complexmentioning
confidence: 99%